Coronary Large Conductance Ca2+-Activated K+ Channel Dysfunction in Diabetes Mellitus - Lu, Tong; Lee, Hon-Chi (Frontiers in Physiology, 2021)
Diabetes mellitus is an independent risk of macrovascular and microvascular complications, while cardiovascular diseases remain a leading cause of death in both men and women with diabetes. Large conductance Ca2+-activated K+ (BK) channels are abundantly expressed in arteries and are the key ionic determinant of vascular tone and organ perfusion. It is well-established that the downregulation of vascular BK channel function with reduced BK channel protein expression and altered intrinsic BK channel biophysical properties is associated with diabetic vasculopathy. Recent efforts also showed that diabetes-associated changes in signaling pathways and transcriptional factors contribute to the downregulation of BK channel expression. This manuscript will review our current understandings on the molecular, physiological, and biophysical mechanisms that underlie coronary BK channelopathy in diabetes mellitus.